PENERAPAN VPN CLIENT SERVER DALAM SISTEM PRESENSI SIDIK JARI SEBAGAI INDIKATOR KINERJA KARYAWAN - Nuris Setiawan (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
The rapid development of technology gives rise to a variety of modern tools that are able to support the smoothness and increase the efficiency of work in a business field. One of the various tools is a fingerprint scanner or commonly referred to as a fingerprint detector. This tool can be used to serve as a presence support which is certainly related to the pattern or level of work discipline. This is what is trying to be applied to CV Karina Indah Pekalongan. CV Karina Indah is a line of business engaged in transportation and has 3 branch offices. Where with the 3 branch offices located in different cities, it will be difficult to control the discipline of their employees at work. In addition, Karina Indah's CV still uses the manual presence method. That is still using signatures on each employee when making attendance. It is very possible that there will be manipulation of attendance data by employees. Therefore, seeing the problems that occur, the author has the idea and initiative to create an automated presence system in the form of writing a thesis entitled "Implementation of a VPN Client Server-Based Fingerprint Attendance System (Case Study of CV Karina Indah Pekalongan)". In designing this computerized presence system, the author uses the Microsoft Visual Basic 6.0 programming language. It is hoped that the presence of this new presence system can increase the efficiency of employees at work.